Hubungan Manajemen Ketatausahaan (TU) Dengan Kearsipan Sekolah di SMA Negeri 1 Praya Timur Kabupaten Lombok Tengah Tahun pelajaran 2022 - Aryani, Menik (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2023)
The problem formulation in this research,  there is Relationship between Administration Management (TU) With School Filing At SMAN 1 east praya district central lombok  in the academic Year 2017/2018.  The purpose of this study is to Know Relationship between Administration Management (TU) With School Filing At SMAN 1 east praya district central lombok  in the academic Year 2017/2018. The method used in this research is quantitative research method because it has fulfilled the scientific principles that is concrete / empirical, Data collection method used in this research is by questionnaire and documentation method. Data analysis method used is statistical analysis method with product moment correlation coefficient formula. Based on the results of data analysis in this study, obtained rcount value of 0.563, then the value is consulted with the value of rtable product moment at the level of significance of 5% with N = 15 obtained value of 0.563. This fact shows that r count is bigger than r table or 0,563> 0,514, hence result of data analysis in this research stated significant.Thus it can be concluded that there is Relationship between Administration Management (TU) With School Filing At SMAN 1 east praya district central lombok  in the academic Year 2017/2018, with medium category.Key Words: Administration Management, and Archives of School